Chronic kidney disease, cerebral blood flow, and white matter volume in hypertensive adults. (29th March 2016) - Kurella Tamura, Manjula; Pajewski, Nicholas M.; Bryan, R. Nick; Weiner, Daniel E.; Diamond, Matthew; Van Buren, Peter; Taylor, Addison; Beddhu, Srinivasan; Rosendorff, Clive; Jahanian, Hesamoddin; Zaharchuk, Greg
Abstract : Objective: To determine the relation between markers of kidney disease—estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR)—with cerebral blood flow (CBF) and white matter volume (WMV) in hypertensive adults. Methods: We used baseline data collected from 665 nondiabetic hypertensive adults aged ≥50 years participating in the Systolic Blood Pressure Intervention Trial (SPRINT). We used arterial spin labeling to measure CBF and structural 3T images to segment tissue into normal and abnormal WMV. We used quantile regression to estimate the association between eGFR and UACR with CBF and abnormal WMV, adjusting for sociodemographic and clinical characteristics. Results: There were 218 participants (33%) with eGFR <60 mL/min/1.73 m 2 and 146 participants (22%) with UACR ≥30 mg/g. Reduced eGFR was independently associated with higher adjusted median CBF, but not with abnormal WMV. Conversely, in adjusted analyses, there was a linear independent association between UACR and larger abnormal WMV, but not with CBF. Compared to participants with neither marker of CKD (eGFR ≥60 mL/min/1.73 m 2 and UACR <30 mg/g), median CBF was 5.03 mL/100 g/min higher (95% confidence interval [CI] 0.78, 9.29) and abnormal WMV was 0.63 cm 3 larger (95% CI 0.08, 1.17) among participants with both markers of CKD (eGFR <60 mL/min/1.73 m 2 and UACR ≥30 mg/g). Conclusions: Among nondiabetic hypertensive adults, reduced eGFR was associated with higher CBF and higher UACR was associated with larger abnormal WMV.